Single-Session Surgical Intervention with Resection of a Primary Cranial Osteosarcoma and Cranioplasty using a 3D-Printed Craniotomy Template and Cranioplasty Molds - Duda, Sven; Ivanyi, Philipp; Omar, Mohamed; Hartmann, Christian; Musienko, Eugen; Wessling, Heinrich (Journal of Neurological Surgery Reports, 2025)
Although osteosarcomas are the most frequent primary malignant bone tumors, the primary cranial manifestation of this condition is very rare with only a limited number of cases presented in the literature.We present the case of a 20-year-old male patient who underwent single-session surgical intervention for resection of right frontal osteosarcoma with a tailor-made craniotomy and cranioplasty using virtually designed 3D-printed templates and molds. Subsequently, the patient was treated according to the EURAMOS protocol and received adjuvant systemic chemotherapy.At 18-month follow-up, the patient was clinically asymptomatic, and both the magnetic resonance imaging scan of the head and the staging computed tomography showed no signs of tumor recurrence or metastases. The case presented shows that the use of 3D-printed molds facilitate a safe preoperative planning of the resection area and a single-session surgery including a custom-made cranioplasty responding to the highest esthetical standards.
Keywords: cranial osteosarcoma; 3D printing; EURAMOS; craniofacial osteosarcoma